THE HARMONIOUS BLEND OF CULTURAL ACCULTURATION AND ISLAMIC PRINCIPLES WITHIN THE RICH TAPESTRY OF JAMBIâ€™S RELIGIOUS TRADITIONS - Zulgafrin, Zulgafrin (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2023)
ABSTRACTThis research was carried out to determine Islamic contact with the Malay community in Jambi, through Arab traders and Sufis who entered the area across Jambi City. Apart from that, we also know the process of interaction between Islam and community culture which ultimately gave birth to acculturation to Malay culture and Islamic values. The method used in the research is the historical research method to reveal the history of the entry of Islam into the people of Seberang Jambi City. Research stages include heuristics, criticism, interpretation and historiography. The research results show that the interaction of Islam and Malay society gave birth to acculturation of Islamic culture and values. The acculturation process is through trade relations, marriage, and interactions in adjacent communities. It can be seen in the religious traditions across the city of Jambi, such as in the Malay traditional seloko which contains Islamic values. Apart from that, religious rituals also developed in Jambi Malay society, such as assyuro commemoration, grave pilgrimage, nuak ketan, baby thanksgiving and nisfu Sya'ban, and in artistic traditions including Gambus, zapin dance, Dana Syarah and Hadrah dance.Keywords: Acculturation, Islam and Malay Culture, Religious Culture.Â ABSTRAKPenelitian ini dilakukan untuk mengetahui kontak Islam dengan masyarakat Melayu di Jambi, melalui para pedagang Arab dan para Sufi yang masuk ke wilayah seberang Kota Jambi. Selain itu kita juga mengetahui proses interaksi antara Islam dan budaya masyarakat yang pada akhirnya melahirkan akulturasi budaya Melayu dan nilai-nilai Islam. Metode yang digunakan dalam penelitian adalah metode penelitian sejarah untuk mengungkap sejarah masuknya Islam ke masyarakat Seberang Kota Jambi. Tahapan penelitian meliputi heuristik, kritik, interpretasi dan historiografi. Hasil penelitian menunjukkan bahwa interaksi Islam dan masyarakat Melayu melahirkan akulturasi budaya dan nilai-nilai Islam. Proses akulturasi tersebut melalui hubungan dagang, perkawinan, dan interaksi dengan masyarakat yang berdekatan. Hal ini terlihat pada tradisi keagamaan yang ada di Kota Jambi, seperti pada seloko adat melayu yang mengandung nilai-nilai keislaman. Selain itu, ritual keagamaan juga berkembang pada masyarakat Melayu Jambi, seperti peringatan assyuro, ziarah kubur, nuak ketan, syukuran bayi dan nisfu Sya'ban, serta dalam tradisi kesenian antara lain Gambus, tari zapin, Dana Syarah, dan tari Hadrah.Kata Kunci: Akulturasi, Islam dan Budaya Malayu, Budaya Beragama